Characteristics of decomposed waste in landfill - Bari, Md. Niamul; Alam, Md. Zahangir; Jamal, Parveen (2007)
A thorough laboratory investigation is carried out to determine the characteristics of decomposed waste of municipal solid waste dumping site of Rajshahi City Corporation. Samples are collected from various depths by driving PVC pipe in different locations of the dumping site. A rigorous laboratory analysis on collected samples reveals that the concentrations of most of the constituents are higher in all depths compared to Bangladesh Environmental Quality Standard. In the case of heavy metal like Lead and Cadmium, the concentration upto 4.5 ft depth goes beyond the toxic limit. The concentrations of all constituents are decreasing trend in higher depths of fill. The constituents of the higher depths are percolated more through the unlined bottom of this crude dumping site. The decomposed waste at the crude dumping site and also other places after replacing has a potential threat of groundwater and surface water pollution.